Influence of cell culture-derived media and environmental contaminants on the effect of feline calicivirus inactivation agents - Rei Saito; Shiori Katta; Takeshi Takizawa; Junichi Sugiyama; Yasushi Kakizawa; Shigeru Morikawa (Scientific Reports)
Abstract Several studies on viral inactivation agents frequently overlook the influence of virus suspension conditions, which often leads to inconsistent conclusions. We investigated the impact of cell culture-derived media and environmental contaminants on the efficacy of viral inactivation agents against feline calicivirus (FCV). The FCV in Eagle’s minimum essential medium (EMEM) with cell-derived metabolites, was replaced with distilled water (DW) with using a column-based simple dispersant replacement method. Sodium dodecyl sulfate (SDS) or sodium hypochlorite (NaClO) were less effective against FCV in EMEM than DW, while didecyl dimethylammonium chloride (DDAC) was more effective. The inactivation effect of 50% v/v ethanol was stronger against FCV in EMEM than DW, whereas that of 70% v/v ethanol was more effective in DW. Analysis of the effect of EMEM components revealed that inorganic salts and basic amino acids (BAA) reduced SDS inactivation efficacy but enhanced DDAC’s. Similarly, inorganic salts reduced the effect of 70% v/v ethanol, while amino acids, especially BAA reduced that of NaClO’s. Since each inactivating agent affects FCV differently, the influence of each EMEM component is assumed to differ. Moreover, environmental contaminants, such as bovine serum and saliva, reduced the overall effectiveness of the agents owing to their inorganic substances and proteins.